The role of trade unions in advancing a just transition‘ in South Africa: a case of COSATU‘s perspective and approach to climate change - Zulu, Onginkosi Paul (My University, 2021)
This research report analyzes the the methods through which the COSATU climate change policy was developed. The broad topic looks at the role of trade unions in advancing a just transition‘ in South Africa: A case of COSATU‘s perspective and approach to climate change. In 2009 COSATU took a resolution to pursue a just transition towards a low carbon and climate resilient society. Upon adopting the resolution, the COSATU Central Executive Committee (CEC) mandated NALEDI to conduct research on climate change, looking at the impact of climate change on the workers, and also to develop a Climate Change Policy Framework. NALEDI formed a Climate Change Reference group in 2010 which then developed a Policy Framework which was endorsed by the CEC in 2011. Following the endorsement of the policy framework, the COSATU Climate Change Policy document was developed and it was adopted at the 2012 COSATU National Congress. The study focuses on COSATU‘S perspective and approach to climate change and just transition. The aim of the study was to find out how committed is COSATU to its climate change policy and to its 2009 resolution of pursuing a just transition towards a low carbon and climate-resilient society, which was endorsed in the COSATU 2012 congress. I explored this broad topic by looking at two aspects, namely, the policy formulation process as well as the implementation phase of the policy. This entailed looking at the actual policy formulation process and whether at the COSATU 2012 Congress the policy was debated or the climate change policy was just a project run by technocrats, and whether workers were involved in the policy formulation process, if so, to what extent were they involved. I also looked at what were the discussions on the Policy Framework on climate change; how was the Policy Framework on climate change tabled at the COSATU congress; what were the discussion prior to the endorsement the policy framework; how was the resolution which endorsed the policy framework reached; who drafted the resolution; what were the plenary discussions around the adoption of a just transition to low carbon and climate – resilient society; what were the concerns raised at plenary; why was the resolution crafted the way it was crafted; who were the people involved in the process of formulating COSATU‘s policy on climate change, was it just a handful policy experts or were the trade unions involved; what were the different considerations during the actual drafting of the COSATU climate change policy document; how was the process rolled out and what were the challenges? In this study I used ecological Marxism mixed with eco-socialism as well as a notion of an active consciousness to identify and to resist the systematic elements of fossil capitalism‘ as my theoretical framework. This theoretical framework was used to assess the methods through which COSATU climate change policy was developed and also in analyzing fossil capitalism as well as the just transition. In a nutshell the study found that: The reference group consisted of trade union officials, shop stewards, environmental organizations and academics. While COSATU is an independent federation of trade unions in South Africa, the resolution to pursue a just transition towards a low carbon and a climate resilient society was greatly and directly influenced by ITUC, and also by ITF (via SATAWU) who started conducting research on CO2 emissions in the 2000s. Issues were robustly debated in reference group meetings; members of the reference group attended seminars on the climate crisis; 3 research reports in the Mining Sector, Poultry Sector and Chemicals Sector were finalized; capacity building and information sharing workshops were held with shop stewards, where subject experts were invited to do presentations and where the content of the policy document was endorsed. In developing the climate change policy document COSATU followed the International Labour Organization (ILO) guidelines which are designed at helping trade unions to formulate policies. Through this process COSATU undoubtedly produced a brilliant climate change policy document. COSATU‘s position supports a deep transformative change in theory (climate change policy document) but in practice it promotes a narrow reformist transformation and little or no action has been taken to further advance the policy commitments. The COSATU through its climate change policy document adopted 15 principles that profess to tackle the climate crisis in South Africa and also calls for regional solidarity. COSATU has not taken a lead role in any of the initiatives advanced in the policy document. COSATU had taken a top to bottom policy approach but on the contrary, an alternative to capitalism as well as the transition to a just transition towards a low carbon and a climate resilient society have to be built by activists from the bottom-up. Workers were only consulted when in-depth research was done in the Poultry, Chemicals and Mining sectors, after the policy framework was endorsed by CEC in 2011 and after the Climate Change Policy was adopted in the 2012 COSATU National Congress. COSATU website has posted an article by Ian Angus, titled ―Confronting the Climate Change Crisis, An Ecosocialist Perspective‖ yet eco-socialism remains a utopian project within COSATU and it has never been pursued by COSATU. COSATU adopted 15 policy principles in the climate change policy document. These principles are mainly COSATU ecological commitment to fighting fossil capitalism, and to pursuing a just transition to a low carbon and climate resilient economy. However, these principles have not been vigorously pursued by COSATU and its affiliates. COSATU currently supports the accumulative imperative. COSATU has adopted a minimalist approach to just transition. Apart from the policy document; the research in 3 sectors and few workshops conducted by the NALEDI reference group, COSATU has not given any support to affiliates in terms of just transition initiative and implementation of the 15 policy principles. The COSATU affiliates do not have the capacity to deal with climate change. The affiliate leaders not educated on climate change. The affiliates do not have environmental policies in place. COSATU supports coal jobs as well as other carbon intensive jobs. COSATU is still engaged in extractivist politics yet the world is busy phasing out coal. Some affiliates within COSATU are in favor socially owned renewable energies yet COSATU supports state owned renewable energies while some affiliates within COSATU are in favor of Nuclear energy. Although COSATU sits at NEDLAC it has not taken the opportunity to advance any of the principles in its policy document due to its stance to defend jobs, including those in carbon intensive industries. COSATU seems oblivious to the metabolic rift that widens even further as a result of inaction. On the overall the study makes some interesting empirical contributions. Consequently, the study is important not only to the labour movement but also it is important to the country as a whole, as it addresses one of the most pressing issue which faces the present generation, and which surely impact future generations. The manner in which the present generation of trade unionists, corporations and communities respond to climate change will influence future responses and the quality of life for Planet Earth‘s inhabitants and all ecosystems.
A research report is submitted in partial fulfilment of the Master of Arts to the Faculty of Humanities, University of the Witwatersrand, 2021